Intra-Articular Giant Heterotopic Ossification following Total Knee Arthroplasty for Charcot Arthropathy. (15th September 2013) - Nakajima, Arata; Tsuge, Shintaro; Aoki, Yasuchika; Sonobe, Masato; Shibata, Yoshifumi; Sasaki, Yu; Nakagawa, Koichi
Abstract : Although the Charcot arthropathy may be associated with serious complications, total knee arthroplasty (TKA) is the preferred choice of treatment by patients. This case report presents an 80-year-old man with intra-articular giant heterotopic ossification following loosening of femoral and tibial implants and femoral condylar fracture. He had undergone TKA because of Charcot neuropathy seven years ago and had been doing well since. Immediately after a left knee sprain, he became unable to walk. Because he had developed a skin ulcer on his left calf where methicillin-resistant Staphylococcus aureus was detected, we postponed revision surgery until the ulcer was completely healed. While waiting, intra-articular bony fragments grew larger and formed giant heterotopic ossified masses. Eventually, the patient underwent revision surgery, and two major ossified masses were carefully and successfully extirpated. It should be noted that intra-articular heterotopic giant ossification is a significant complication after TKA for neuropathic arthropathy.